Sexual Offences Against Women: India's Legal Perspective - Ashok Kumar Behera (IJCLS (Indonesian Journal of Criminal Law Studies), 2021)
The concept of equality and nondiscrimination is placed on account of the Indian constitution. Besides, it also enables the state to adopt different measures of affirmative discrimination in favor of women. Laws tend to be gradual, focusing on detailed forms of brutality rather than dealing expansively with all forms of hostility against women. When the law is input, there is frequently feeble law enforcement. Complementary to that the stable throws away to the woman's children, which as an element from having an adverse result on their health also creates an emotional background for them in which they cannot protect against any bodily bloodshed or a number of forms of injustices.